Nontuberculous Mycobacteria: An Underestimated Cause of Bioprosthetic Valve Infective Endocarditis - Bouchiat, Coralie (Open Forum Infect Dis, 2015)
Background. Atypical mycobacteria, or nontuberculous mycobacteria (NTM), have been barely reported as infective endocarditis (IE) agents. Methods. From January 2010 to December 2013, cardiac valve samples sent to our laboratory as cases of blood culture-negative suspected IE were analyzed by 16S rDNA polymerase chain reaction (PCR). When positive for NTM, hsp PCR allowed species identification. Demographic, clinical, echocardiographic, histopathological, and Ziehl-Neelsen staining data were then collected. Results. Over the study period, 6 of 370 cardiac valves (belonging to 5 patients in 3 hospitals) were positive for Mycobacterium chelonae (n = 5) and Mycobacterium lentiflavum (n = 1) exclusively on bioprosthetic material. The 5 patients presented to the hospital for heart failure without fever 7.1–18.9 months (median 13.1 months) after biological prosthetic valve implantation. Echocardiography revealed paravalvular regurgitation due to prosthesis dehiscence in all patients. Histopathological examination of the explanted material revealed inflammatory infiltrates in all specimens, 3 of which were associated with giant cells. Gram staining and conventional cultures remained negative, whereas Ziehl-Neelsen staining showed acid-fast bacilli in all patients. Allergic etiology was ruled out by antiporcine immunoglobulin E dosages. These 5 cases occurred exclusively on porcine bioprosthetic material, revealing a statistically significant association between bioprosthetic valves and NTM IE (P < .001). Conclusions. The body of evidence confirmed the diagnosis of prosthetic IE. The statistically significant association between bioprosthetic valves and NTM IE encourages systematic Ziehl-Neelsen staining of explanted bioprosthetic valves in case of early bioprosthesis dysfunction, even without an obvious sign of IE. In addition, we strongly question the cardiac bioprosthesis conditioning process after animal sacrifice.